Slurry for battery diaphragm, thermal response safety diaphragm, application of thermal response safety diaphragm and thermal response safety lithium ion battery
By using electrolyte containing thermally responsive safety diaphragms containing microspheres A and microspheres B in lithium-ion batteries, the safety problems of the battery in extreme cases are solved, and the energy efficiency and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202411753955.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Existing thermally responding safety lithium-ion batteries cannot effectively ensure battery safety in extreme cases, and their energy efficiency and cycle life are insufficient.
A slurry for a battery separator containing microspheres A and microspheres B is used to form a thermally responsive safety separator by coating, and a thermally responsive electrolyte of thermally polymerized monomer is used to cut off the internal ion channel of the battery.
When the battery is thermally out of control, it quickly transforms the liquid electrolyte into a solid state, cuts off the ion channel, avoids smoke, fire, and explosion of the battery, and improves the battery's circulation performance, rate performance and energy efficiency.
Smart Images

Figure CN119674442A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a slurry for battery diaphragms, a thermally responsive safety diaphragm and applications thereof, and a thermally responsive safety lithium-ion battery. Background Art
[0002] Since its introduction, lithium-ion batteries have been widely used in many fields due to their high energy density and long cycle life. In recent years, due to the shortage of fossil energy and other reasons, the development of renewable energy technologies such as photovoltaic and wind power generation has received more and more attention, which has once again promoted the large-scale application of lithium-ion batteries in the field of energy storage.
[0003] Due to cost, safety and environmental considerations, lithium iron phosphate batteries are currently the most widely used energy storage batteries. However, they are still likely to cause safety accidents under external thermal, mechanical and electrical abuse scenarios, posing a huge challenge to the safe and stable operation of energy storage systems.
[0004] By using an electrolyte containing an initiator and a thermally polymerizable monomer, a lithium-ion battery with a thermal response function can be prepared, which can initiate electrolyte polymerization before the battery has a serious thermal runaway, thereby cutting off the ion channels inside the battery and alleviating the gas generation problem of the liquid electrolyte. However, due to the lack of long-term stability of the initiator used in the thermally responsive electrolyte under light and room temperature, it has a serious impact on the energy efficiency and cycle life of the battery, and there is currently no good solution.
[0005] CN112615107A discloses a microsphere, a diaphragm containing the microsphere, and a lithium ion battery containing the diaphragm, wherein the microsphere has a core-shell structure, an average particle size of 0.01 μm-10 μm, the material forming the shell layer includes a thermosensitive polymer, and the material forming the core includes a conductive material; wherein the thermosensitive polymer is selected from polyethylene, polypropylene, etc., the conductive material is a polymer material doped and / or undoped with an electron acceptor, and the microsphere also contains ceramic particles such as silicon dioxide. That is, the technical solution is to adopt a polymer directional design coating method, screen thermosensitive polymer coated conductive materials, and coat microspheres containing thermosensitive polymer coated conductive materials on the surface of the diaphragm without affecting the performance of the lithium ion battery, which can effectively improve the high temperature safety performance of the lithium ion battery, but it mainly ensures the safety of the battery by slowly releasing energy through a micro short circuit inside the battery, and cannot effectively cut off the ion path inside the battery, so it cannot ensure the safety of the battery under extreme conditions such as acupuncture or rapid temperature rise, and also has the defect of increasing the risk of short circuit inside the battery. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of low energy efficiency and short cycle life of thermal response safety lithium ion batteries in the prior art.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a slurry for a battery separator, wherein the slurry contains microspheres A, microspheres B, a thickener and a binder;
[0008] Wherein, based on the total weight of the slurry, the content of the microsphere A is 30-50wt%, the content of the microsphere B is 25-48wt%, the content of the thickener is 5-15wt%, and the content of the binder is 3-17wt%;
[0009] The material forming the microsphere A includes initiator A; the material forming the microsphere B includes initiator B;
[0010] The initiator A is a peroxide;
[0011] The initiator B is selected from at least one of oxalic acid, glucose, N,N-dimethylaniline, cyclopentaneate, n-dodecyl mercaptan, triethylaluminum and triethylboron;
[0012] The particle size D of the microsphere A and the microsphere B 50 Each independently is 0.05-5 μm.
[0013] A second aspect of the present invention provides a thermally responsive safety diaphragm, the diaphragm comprising a base film and a thermally responsive safety coating coated on the upper and lower surfaces of the base film;
[0014] The thermally responsive safety coating is formed from the slurry for battery separators described in the first aspect.
[0015] The third aspect of the present invention provides the use of the thermally responsive safety separator described in the second aspect in a lithium-ion battery.
[0016] The fourth aspect of the present invention provides a thermally responsive safety lithium-ion battery, the lithium-ion battery comprising: a positive electrode sheet, a negative electrode sheet, a thermally responsive electrolyte and a thermally responsive safety diaphragm; the thermally responsive electrolyte contains a thermally polymerizable monomer;
[0017] The thermally responsive safety diaphragm is the thermally responsive safety diaphragm described in the second aspect.
[0018] Through the above technical solution, the present invention has at least the following advantages:
[0019] The thermally responsive safety diaphragm formed by coating the battery diaphragm slurry provided by the present invention is applied to lithium-ion batteries containing thermally polymerized monomers. The thermally responsive safety lithium-ion battery can operate normally under conventional working conditions, but during battery thermal runaway, the internal liquid electrolyte will quickly turn into a solid state, thereby cutting off the internal ion channel and preventing the battery from smoking, catching fire, and exploding. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a battery cycle performance test result diagram of a thermally responsive safe lithium-ion battery prepared in an application example of the present invention;
[0021] Figure 2 This is a battery rate performance test result diagram of a thermally responsive safe lithium-ion battery prepared in an application example of the present invention;
[0022] Figure 3 This is a battery energy efficiency test result diagram of a thermally responsive safe lithium-ion battery prepared in an application example of the present invention;
[0023] Figure 4 This is a battery thermal response safety test result diagram of a thermal response safety lithium ion battery prepared in an application example of the present invention;
[0024] Figure 5 These are scanning electron microscope images of microsphere A prepared in Preparation Example 1 of the present invention at different magnifications. DETAILED DESCRIPTION
[0025] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0026] In the present invention, "EC" means ethylene carbonate, "DMC" means dimethyl carbonate, and "EMC" means ethyl methyl carbonate.
[0027] In the present invention, 1M means "1 mol / L".
[0028] As mentioned above, the first aspect of the present invention provides a slurry for a battery separator, the slurry containing microspheres A, microspheres B, a thickener and a binder;
[0029] Wherein, based on the total weight of the slurry, the content of the microsphere A is 30-50wt%, the content of the microsphere B is 25-48wt%, the content of the thickener is 5-15wt%, and the content of the binder is 3-17wt%;
[0030] The material forming the microsphere A includes initiator A; the material forming the microsphere B includes initiator B;
[0031] The initiator A is a peroxide;
[0032] The initiator B is selected from at least one of oxalic acid, glucose, N,N-dimethylaniline, cyclopentaneate, n-dodecyl mercaptan, triethylaluminum and triethylboron;
[0033] The particle size D of the microsphere A and the microsphere B 50 Each independently is 0.05-5 μm.
[0034] Preferably, the peroxide is selected from at least one of cumene hydroperoxide, tert-butyl hydroperoxide, dicumyl peroxide, di-tert-butyl peroxide, dibenzoyl peroxide, dodecyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diisopropyl peroxydicarbonate and dicyclohexyl peroxydicarbonate, more preferably at least one of dicumyl peroxide, cumene hydroperoxide and di-tert-butyl peroxide, further preferably dicumyl peroxide.
[0035] Preferably, the initiator B is selected from at least one of N,N-dimethylaniline, n-dodecyl mercaptan and glucose, preferably N,N-dimethylaniline.
[0036] Preferably, the particle size D of the microsphere A and the microsphere B is 50 Each independently 1-2 μm.
[0037] Preferably, the materials forming the microspheres A and B further include hollow mesoporous materials and phase change materials; wherein,
[0038] The hollow mesoporous material is selected from silica and / or a polymer I with a weight average molecular weight of 10,000 to 1,000,000, and the polymer I is selected from at least one of polymethyl acrylate, polymethyl methacrylate, polyamide and polystyrene, more preferably at least one of silica, polymethyl methacrylate and polystyrene, and further preferably polymethyl methacrylate;
[0039] The phase change material is selected from at least one of hydrated sulfate, n-dodecane, n-docosane, 6-methyldodecane, 8-methyldocosane and a high molecular weight polymer ⅠⅠ with a weight average molecular weight of 2,000-50,000, and the high molecular weight polymer ⅠⅠ is selected from at least one of polyethylene, polypropylene, polyethylene glycol and polyoxymethylene.
[0040] Under the above preferred conditions, the technical solution provided by the present invention can obtain a lithium-ion battery with superior cycle performance, rate performance, energy efficiency and safety performance.
[0041] Preferably, the hydrated sulfate is magnesium sulfate heptahydrate and / or sodium sulfate decahydrate.
[0042] Further preferably, the phase change material is at least one of polyethylene, polypropylene and polyoxymethylene, and most preferably polyethylene.
[0043] Preferably, the particle size D of the hollow mesoporous material is 50It is 0.05-5 μm, preferably 1-2 μm.
[0044] According to a preferred embodiment, the microsphere A is prepared by a method comprising the following steps:
[0045] (1) In the presence of ethanol, a phase change material and an initiator A are contacted and mixed I to obtain a mixed solution;
[0046] (2) The mixed solution is contacted and mixed with a hollow mesoporous material to obtain the microsphere A.
[0047] Preferably, the weight ratio of the phase change material, the initiator A and the hollow mesoporous material is 1:0.2-0.7:0.05-0.15.
[0048] Preferably, relative to 1 g of the phase change material, the amount of ethanol used is 2-8 mL.
[0049] Preferably, the conditions of the contact mixing I include: temperature of 30-60° C. and time of 5-15 min.
[0050] Preferably, the contact mixing conditions include: temperature of 30-60°C and time of 45-75 min.
[0051] According to a particularly preferred embodiment, the preparation step of the microspheres A further comprises: in step (2), drying the product obtained by the contact mixing II, centrifuging and washing the product in sequence.
[0052] The present invention has no special requirements for the conditions of drying, centrifugation and washing, and those skilled in the art may use conventional operating methods.
[0053] According to a preferred embodiment, the microspheres B are prepared by a method comprising the following steps:
[0054] (1) In the presence of ethanol, a phase change material and an initiator B are contacted and mixed I to obtain a mixed solution;
[0055] (2) The mixed solution is contacted and mixed with a hollow mesoporous material to obtain the microspheres B.
[0056] Preferably, the weight ratio of the phase change material, the initiator B and the hollow mesoporous material is 1:0.2-0.7:0.05-0.15.
[0057] Preferably, relative to 1 g of the phase change material, the amount of ethanol used is 2-8 mL.
[0058] Preferably, the conditions of the contact mixing I include: temperature of 30-60° C. and time of 5-15 min.
[0059] Preferably, the contact mixing conditions include: temperature of 30-60°C and time of 45-75 min.
[0060] According to a particularly preferred embodiment, the preparation step of the microspheres B further comprises: in step (2), the product obtained by the contact mixing II is dried and then centrifuged and washed in sequence.
[0061] As mentioned above, the second aspect of the present invention provides a thermally responsive safety diaphragm, which includes a base film and a thermally responsive safety coating coated on the upper and lower surfaces of the base film;
[0062] The thermally responsive safety coating is formed from the slurry for battery separators described in the first aspect.
[0063] Preferably, the thermally responsive safety diaphragm is prepared by a method comprising the following steps:
[0064] (S1) mixing microspheres A, microspheres B, a thickener (hydroxymethyl cellulose) and a binder (styrene-butadiene rubber) to obtain the battery separator slurry;
[0065] (S2) coating the battery separator slurry on a base film and drying the base film to obtain the thermally responsive safety separator.
[0066] The amounts of the thermally responsive microspheres A, the thermally responsive microspheres B, the thickener and the binder are the same as the contents of the components in the battery separator slurry described in the first aspect, and are not described in detail here.
[0067] Preferably, the mixing conditions include: a rotation speed of 400-600 rpm and a time of 4-6 hours.
[0068] Preferably, the drying conditions include: temperature of 40-70 rpm and time of 10-14 h.
[0069] Preferably, the coating method is a blade coating method.
[0070] Preferably, the base membrane is a polyolefin membrane.
[0071] As mentioned above, the third aspect of the present invention provides the use of the thermally responsive safety separator described in the second aspect in a lithium-ion battery.
[0072] As mentioned above, the fourth aspect of the present invention provides a thermally responsive safety lithium-ion battery, which includes: a positive electrode sheet, a negative electrode sheet, a thermally responsive electrolyte and a thermally responsive safety diaphragm; the thermally responsive electrolyte contains a thermally polymerizable monomer;
[0073] The thermally responsive safety diaphragm is the thermally responsive safety diaphragm described in the second aspect.
[0074] Preferably, the thermally polymerizable monomer is at least one selected from methyl acrylate, methyl methacrylate, styrene, vinylene carbonate, butadiene, chloroprene and acrylonitrile, and more preferably vinylene carbonate.
[0075] The present invention will be described in detail below through examples. In the following examples, unless otherwise specified, the raw materials and equipment used are all commercially available, and the solvents used are all analytically pure.
[0076] Polyethylene: CAS number 9002-88-4, weight average molecular weight 2,000-3,000, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0077] Polypropylene: CAS number 9003-07-0, weight average molecular weight 6,000-8,000, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0078] Polyoxymethylene: CAS number 9002-81-7, weight average molecular weight 10,000-12,000, purchased from Shanghai Titan Technology Co., Ltd.;
[0079] Cumene hydroperoxide: CAS number 80-15-9, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0080] Diisopropylbenzene peroxide: CAS number 80-43-3, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0081] Di-tert-butyl peroxide: CAS No. 110-05-4, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0082] Glucose: CAS number 50-99-7, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0083] N,N-Dimethylaniline: CAS number 121-69-7, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0084] n-Dodecanethiol: CAS number 112-55-0, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0085] Silicon dioxide: purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0086] Polymethyl methacrylate: weight average molecular weight 10,000-15,000, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0087] Polystyrene: weight average molecular weight 10,000-15,000, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0088] Methyl methacrylate: CAS number 80-62-6, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0089] Vinylene carbonate: CAS number 872-36-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0090] Dibenzoyl peroxide: CAS number 94-36-0, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0091] Commercial lithium-ion battery electrolyte: The specific composition is a combination of 1M LiPF6 and EC, DMC, and EMC (V EC :V DMC :V EMC =1:1:1), purchased from Farnlight New Energy Technology Co., Ltd.;
[0092] Polyolefin diaphragm: Celgard2400 diaphragm, 25 μm thick, single-layer PP material, 41% porosity, purchased from Celgard Company, USA;
[0093] Commercial lithium iron phosphate cathode: surface density is 12 mg / cm 2 , active substances accounted for 95.4wt%, purchased from Shenzhen Kejing Zhida Technology Co., Ltd.;
[0094] Commercial graphite anode: surface density 5.8 mg / cm 2 , active substances accounted for 95.5wt%, purchased from Shenzhen Kejing Zhida Technology Co., Ltd.
[0095] In the following examples, room temperature refers to 23±2°C.
[0096] In the following examples, the scanning electron microscope images were obtained by testing using a Zeiss GeminiSEM 360 scanning electron microscope.
[0097] The following preparation examples are used to illustrate the preparation methods of microspheres A and B of the present invention.
[0098] Preparation Example 1
[0099] (1) In the presence of 2 mL of hot ethanol, 400 mg of the phase change material and 200 mg of the initiator A were dissolved and stirred to perform contact mixing I (temperature of 50° C., time of 10 min) to obtain a mixed solution;
[0100] (2) adding 40 mg of hollow mesoporous material to the mixed solution for contact mixing ⅠⅠ (temperature 50°C, time 60 min);
[0101] Subsequently, the product was transferred to a vacuum oven at 50 °C and heated for 30 min, and then centrifuged at a speed of 8000 rpm for 10 min;
[0102] After centrifugation, the microspheres were washed with ethanol three times and then dried at room temperature to obtain microspheres A.
[0103] (3) Substituting an equal mass of initiator B for forming microspheres B for initiator A in step (1) above, and preparing microspheres B using the same preparation method as that for microspheres A.
[0104] The raw material ratios for preparing microspheres A and microspheres B are shown in Table 1.
[0105] Unless otherwise specified, the remaining preparation examples were carried out using a method similar to that of Preparation Example 1, except that different raw material ratios were used. For details, see Table 1.
[0106] Table 1
[0107]
[0108] The following examples are used to illustrate the preparation method of the thermal responsive safety diaphragm of the present invention.
[0109] Example 1 (each 1wt% represents 1mg)
[0110] (1) At room temperature, the microspheres A (40 wt%) prepared in Preparation Example 1 and the microspheres B (40 wt%) prepared in Preparation Example 1 were mixed with a thickener (hydroxymethyl cellulose, 10 wt%) and a binder (styrene-butadiene rubber, 10 wt%) (speed of 500 rpm, time of 5 h) to obtain a uniform and stable slurry for a battery separator;
[0111] (2) The battery separator slurry was coated on the base film (Celgard 2400 separator) by a scalpel coating method and dried at 60° C. for 12 h to obtain a thermally responsive safety separator.
[0112] Embodiment 2-7
[0113] The same method as in Example 1 was used, except that the microspheres A prepared in Preparation Example 1 were replaced with microspheres A prepared in Preparation Example 2, Preparation Example 3, Preparation Example 4, Preparation Example 5, Preparation Example 6, and Preparation Example 7 of equal mass, respectively;
[0114] The microspheres B prepared in Preparation Example 1 were replaced with microspheres B prepared in Preparation Example 2, Preparation Example 3, Preparation Example 4, Preparation Example 5, Preparation Example 6, and Preparation Example 7 of equal mass.
[0115] Thermally responsive safety diaphragms were obtained respectively.
[0116] Comparative Example 1
[0117] The same method as Example 1 was followed, except that microsphere A was not added in this comparative example.
[0118] A thermally responsive safety diaphragm is obtained.
[0119] Comparative Example 2
[0120] The same method as Example 1 was followed, except that microsphere B was not added in this comparative example.
[0121] A thermally responsive safety diaphragm is obtained.
[0122] The following application examples are used to illustrate the preparation method of the thermally responsive safe lithium-ion battery of the present invention.
[0123] Application Example 1
[0124] (1) Combination of 1M LiPF6 with EC, DMC, and EMC (V EC :V DMC :V EMC =1:1:1) adding 25wt% of vinylene carbonate into the electrolyte to obtain a thermally responsive electrolyte;
[0125] (2) A commercial lithium iron phosphate positive electrode, a commercial graphite negative electrode, a thermally responsive electrolyte and the thermally responsive safety diaphragm prepared in Example 1 are assembled into a battery to obtain a thermally responsive safety lithium-ion battery.
[0126] Application Example 2-7
[0127] The same method as Application Example 1 is followed, except that in step (2), the thermally responsive safety diaphragm prepared in Example 1 is replaced by the thermally responsive safety diaphragms prepared in Example 2, Example 3, Example 4, Example 5, Example 6, and Example 7, respectively.
[0128] A thermally responsive and safe lithium-ion battery is obtained.
[0129] Comparative Application Example 1-2
[0130] The same method as in Application Example 1 is used, except that in step (2), the thermally responsive safety diaphragm prepared in Example 1 is replaced by the thermally responsive safety diaphragms prepared in Comparative Example 1 and Comparative Example 2, respectively.
[0131] A thermally responsive and safe lithium-ion battery is obtained.
[0132] Comparative Application Example 3
[0133] The same method as in Application Example 1 was used, except that in step (2), the thermal responsive safety diaphragm prepared in Example 1 was replaced with a commercial Celgard 2400 diaphragm, and the electrolyte used was a combination of 1M LiPF6 and EC, DMC, and EMC (V EC :V DMC :V EMC =1:1:1)+25wt% of vinylene carbonate+1wt% of dibenzoyl peroxide.
[0134] A thermally responsive and safe lithium-ion battery is obtained.
[0135] Comparative Application Example 4
[0136] The same method as in Application Example 1 is used, except that in step (1), the thermal responsive electrolyte is replaced with a commercial lithium-ion battery electrolyte.
[0137] A thermally responsive and safe lithium-ion battery is obtained.
[0138] Test Case
[0139] The thermal response safety lithium-ion battery prepared above is subjected to performance tests, including battery cycle performance test, battery rate performance test, battery energy efficiency test, and battery thermal response safety test. Among them:
[0140] Battery cycle performance test: Wuhan Land charge and discharge tester was used for charge and discharge test. Specifically, within the voltage range of 2.5-3.65V, the battery was activated three times at a rate of 0.1C, and then charged and discharged 50 times at a rate of 0.5C. The test results are shown in Figure 1 .Depend on Figure 1 It can be seen that the cycle performance of the thermally responsive safe lithium-ion batteries prepared in Application Examples 1-7 of the present invention has no obvious deterioration, and is better than the effect of using the commercial Celgard2400 diaphragm and the electrolyte containing initiator and thermally responsive monomer in Comparative Application Example 3, indicating that the thermally responsive diaphragm used has good compatibility with the battery system and does not have the problem of easily causing poor cycle performance in the prior art.
[0141] Battery rate performance test: Wuhan Land charge and discharge tester was used for testing. Specifically, the battery was activated at 0.1C for 3 weeks in the voltage range of 2.5-3.65V, and then cycled at 1C, 2C, 3C, and 1C for 5 weeks. The test results are shown in Figure 2 .Depend on Figure 2It can be seen that the rate performance of the thermally responsive safe lithium-ion batteries prepared in Application Examples 1-7 of the present invention has no obvious deterioration, and is significantly better than the effect of using the commercial Celgard2400 diaphragm and the electrolyte containing initiator and thermal responsive monomer in Comparative Application Example 3, indicating that the thermally responsive diaphragm used has good compatibility with the battery system, and there is no problem of poor rate performance caused by the prior art.
[0142] Battery energy efficiency test: Wuhan Land charge and discharge tester was used for testing. Specifically, the battery was activated at 0.5C for three cycles within the voltage range of 2.5-3.65V, and its average energy efficiency was calculated. The energy efficiency was calculated as follows: (the total discharge energy of 0.5C cycle for three weeks / the total charge energy of 0.5C cycle for three weeks) × 100%. The test results are shown in Figure 3 .Depend on Figure 3 It can be seen that the energy efficiency of the thermally responsive safe lithium-ion batteries prepared in Application Examples 1-7 of the present invention has no obvious decrease, and is significantly better than the effect of using the commercial Celgard2400 diaphragm and the electrolyte containing initiator and thermally responsive monomer in Comparative Application Example 3, indicating that the thermally responsive diaphragm used has good compatibility with the battery system, and there is no problem of energy efficiency degradation that is easily caused by the prior art.
[0143] Battery thermal response safety test: Wuhan Land charging and discharging tester is used for testing. Specifically, external heating test is performed under full charge state, and AC impedance test is used to monitor the change of internal impedance of the battery in real time. The heating temperature is 120℃ and the heating time is 2min. The test results are shown in Figure 4 .Depend on Figure 4 It can be seen that the thermally responsive safe lithium-ion batteries prepared in Application Examples 1-7 of the present invention can respond quickly under external overheating conditions, the battery impedance increases earlier and faster, and the final impedance value is also significantly higher than that of Comparative Application Examples 1-4, indicating that the safety performance of the prepared thermally responsive safe lithium-ion batteries is significantly better than that of the prior art and the comparative examples that are not within the technical solution of the present invention.
[0144] The present invention is exemplarily Figure 5 The scanning electron microscope images of microsphere A prepared in Preparation Example 1 at different magnifications are provided; Figure 5 It can be seen that the microspheres A prepared in Preparation 1 have uniform morphology, intact structure and particle size D 50 This shows that in the preferred case of the present invention, when porous and hollow hollow mesoporous material microspheres with a particle size of 0.05-5 μm are used as core-shell, the initiator is used as the core to fill the hollow mesoporous material, and the phase change material blocks the holes, thereby preparing microspheres A with unchanged particle size.
[0145] It can be seen from the above results that the thermally responsive safety diaphragm formed by coating the battery diaphragm slurry provided by the present invention is applied to lithium-ion batteries containing thermally polymerized monomers. The thermally responsive safety lithium-ion battery can achieve rapid thermal response while ensuring cycle performance, rate performance, and energy efficiency, significantly improving battery safety performance, and does not have the problem of serious deterioration of electrical performance in the prior art.
[0146] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A slurry for battery separator, characterized in that: The slurry contains microspheres A, microspheres B, a thickener and a binder; Wherein, based on the total weight of the slurry, the content of the microsphere A is 30-50wt%, the content of the microsphere B is 25-48wt%, the content of the thickener is 5-15wt%, and the content of the binder is 3-17wt%; The material forming the microsphere A includes initiator A; the material forming the microsphere B includes initiator B; The initiator A is a peroxide; The initiator B is selected from at least one of oxalic acid, glucose, N,N-dimethylaniline, cyclopentaneate, n-dodecyl mercaptan, triethylaluminum and triethylboron; The particle size D of the microsphere A and the microsphere B 50 Each independently is 0.05-5 μm.
2. The slurry according to claim 1, wherein The peroxide is selected from at least one of cumene hydroperoxide, tert-butyl hydroperoxide, dicumyl peroxide, di-tert-butyl peroxide, dibenzoyl peroxide, dodecyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diisopropyl peroxydicarbonate and dicyclohexyl peroxydicarbonate; And / or, the initiator B is selected from at least one of N,N-dimethylaniline, n-dodecyl mercaptan and glucose.
3. The slurry according to claim 1 or 2, wherein: The materials forming the microspheres A and B also include hollow mesoporous materials and phase change materials; wherein, The hollow mesoporous material is selected from silicon dioxide and / or a high molecular weight polymer I with a weight average molecular weight of 10,000 to 1,000,000, and the high molecular weight polymer I is selected from at least one of polymethyl acrylate, polymethyl methacrylate, polyamide and polystyrene; The phase change material is selected from at least one of hydrated sulfate, n-dodecane, n-docosane, 6-methyldodecane, 8-methyldocosane and a high molecular weight polymer ⅠⅠ with a weight average molecular weight of 2,000-50,000, and the high molecular weight polymer ⅠⅠ is selected from at least one of polyethylene, polypropylene, polyethylene glycol and polyoxymethylene.
4. The slurry according to claim 3, wherein The particle size D of the hollow mesoporous material 50 0.05-5μm.
5. The slurry according to claim 3 or 4, wherein The microsphere A is prepared by a method comprising the following steps: (1) In the presence of ethanol, a phase change material and an initiator A are contacted and mixed I to obtain a mixed solution; (2) The mixed solution is contacted and mixed with a hollow mesoporous material to obtain the microsphere A.
6. The slurry according to claim 5, wherein The weight ratio of the phase change material, the initiator A and the hollow mesoporous material is 1:0.2-0.7:0.05-0.
15.
7. The slurry according to claim 5, wherein The conditions of the contact mixing I include: temperature of 30-60°C and time of 5-15min; And / or, the conditions of the contact mixing Ⅱ include: temperature of 30-60°C and time of 45-75 min.
8. A thermally responsive safety diaphragm, characterized in that: The diaphragm includes a base film and a thermally responsive safety coating coated on the upper and lower surfaces of the base film; The thermally responsive safety coating is formed from the slurry for battery separator according to any one of claims 1 to 7.
9. Use of the thermally responsive safety diaphragm according to claim 8 in lithium-ion batteries.
10. A thermally responsive safe lithium-ion battery, characterized in that: The lithium-ion battery comprises: a positive electrode sheet, a negative electrode sheet, a thermally responsive electrolyte and a thermally responsive safety diaphragm; the thermally responsive electrolyte contains a thermally polymerizable monomer; The thermally responsive safety diaphragm is the thermally responsive safety diaphragm according to claim 8.
Citation Information
Patent Citations
Microsphere, diaphragm containing microsphere and lithium ion battery containing diaphragm
CN112615107A
Coating diaphragm for lithium ion batteries
CN109935762A
Preparation method of mesoporous silica water-based ceramic slurry
CN112646444A
Microcapsule, lithium ion battery diaphragm containing microcapsule and lithium ion battery
CN115869866A
Lithium ion battery capable of blocking thermal runaway stage by stage and preparation method of lithium ion battery
CN115939516A